Pendampingan Mahasiswa Program Studi Pendidikan Pancasila dan Kewarganegaraan Universitas Jambi dalam Pembuatan Media Pembelajaran pada Sekolah Pancasila Suku Anak Dalam (SAD) Desa Sekaladi - Ichsan, Muhammad; Tiara Maulia, Siti; Dewi, Nurmalia (Pendidikan Sejarah FKIP Universitas JAMBI, 2023)
Equitable access to education is still a fundamental issue for Indonesia, because the gap in education is still very visible on this earth. One example of people who still have difficulty accessing education is the children of Suku Anak Dalam (SAD) in Sekaladi Village, many factors ultimately prevent these children from having formal education like most children in Indonesia. Sobat Eksplorasi Anak Dalam (SEAD) is then present to develop education for SAD children, they create a calistung program to improve basic knowledge while developing the ability to answer the challenges of the times for them. In 2023 SEAD and the Pancasila and Citizenship Education Study Program of Jambi University collaborated to try to further develop the education program for Suku Anak Dalam children in Sekaladi Village. One of the programs carried out is to create learning media that is more adapted to the character of the Sekaladi Village SAD children. The results are three learning media, namely Snakes and Ladders, Smart Boards and Popup Books, all of which have been implemented and received a very good response from the children.